Utilizing simulation model in large-scale production management - Šnapka, Petr; Mikušová, Marie; Mutinová, Terezie (Univerzita Pardubice, 2014)
Main aim of this paper is to present the simulation model for large-scale production process, where usage of the model helps to simulate the course of production for different dynamic characteristics of workplaces’ operations. This model can be used for both the preparation process of the production and also in the realization process, it means within the framework of operative production management and this way it can contribute to its efficiency. The structure of the model is created by functional blocks and their linkages considering organizational and chronological hierarchy of the actions which are presented as the model’s structure. The theoretical knowledge of regulation, hierarchical system and optimization are the base for the simulation model creation.
Keywords: dynamic behavior; functional blocks; mass production; production process; simulation model